Hasan Tiro of Aceh and His Social History: A Study of Political Communication and Propaganda - Wahyudi, Rizqi; Bakti, Andi M. Faisal; Subhan, Arief; Dahlan, Yasin (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
The purpose of this research is to reveal the propaganda evidence behind Hasan Tiro's communication reality in spreading the narrative of Islamism in Aceh. The method used is descriptive qualitative with a narrative analysis research strategy. The primary sources of this research are Hasan Tiro's books (writings) and speech recordings, which contain Islamist narratives disseminated to his followers. Based on the results of data analysis, this research produces novelty in developing political communication theory, namely Islamic propaganda communication theory with a da'wah maudhu'i approach. This research demonstrates that Hasan Tiro's political communication is religious narrative propaganda, and Hasan Tiro's propaganda narrative construction has the potential power to indoctrinate his followers with the Free Aceh ideology. The religious narrative constructed by Hasan Tiro encompasses jihadist thematic propositions from the Qur'an. This study has a limitation in that it does not include a netnographic analysis of the development of Hasan Tiro's propaganda on social media.